KESADARAN HUKUM PELAKU USAHA MIKRO DAN KECIL (UMK) PRODUK MAKANAN DALAM MELAKSANAKAN SERTIFIKASI HALAL MELALUI SELF DECLARE PERSPEKTIF HUKUM ISLAM DI DESA SEDAU KECAMATAN NARMADA KABUPATEN LOMBOK - Ulfa Unisara; Teti Indrawati Purnamasari; Lalu Fahrizal Cahyadi (Universitas Islam Negeri Mataram, 2024)
This journal is motivated by the large number of business actors in Sedau Village who sell processed products but have not received halal certification. Halal certification through self-declare is recognition of the halalness of a product for micro and small business actors based on statements by business actors regarding the halal status of products based on the conditions set by BPJPH with the requirement that business actors have a companion who has been registered to undergo the halal product process and the determination process halal by the MUI fatwa commission. Halal certification is regulated in Law Number 33 of 2014 concerning Guarantees for Halal Products in article 4 which states that every product that enters, circulates and is traded in the territory of Indonesia must be halal certified. The discussion in this journal is (1) What are the factors that cause a lack of legal awareness of micro and small business actors in carrying out halal certification through self-declaring? (2) What is the review of Islamic law on the legal awareness of micro and small business actors in carrying out halal certification through self-declare?.